Maraknya Perdagangan Satwa Langka Di Era Pandemi Covid-19 Di Indonesia - Dinarjati Eka Puspitasari (PAMALI: Pattimura Magister Law Review, 2022)
Introduction: The era of the COVID-19 pandemic has not stopped the perpetrators of conservation crimes from carrying out their actions. The trade in endangered species, both online and offline, is becoming more and more common. Many cases of trade in endangered animals in Indonesia were carried out during this Covid-19 pandemic. Various types of endangered species that should be protected are actually traded and smuggled illegally. Weak law enforcement is also a crucial problem in resolving cases of trafficking in endangered species.Purposes of the Research:  Efforts and participation by the Government, the community, and environmentalists in controlling the rate of illegal trade in endangered species are increasingly prevalent.Methods of the Research: This research is juridical normative, using various primary and secondary legal materials. Data analysis is descriptive qualitative.Results of the Research: The impact of the trade in endangered species brings ecological and economic losses. Although the impact is quite influential, it does not stop the perpetrators of these conservation crimes from taking action. This is done to gain financial gain personally or illegally in groups. Community participation and government supervision need to be increased in suppressing the rate of increase in the trade of endangered species. Preventive and repressive supervision needs to be carried out as much as possible in breaking the chain of the rampant trade in endangered species that occurs in Indonesia.